From Bhakti to Buddhism: Ravidas and Ambedkar - Bellwinkel Schempp, Maren (2007)
Kanpur holds special importance for the dalit movement since it was the cradle of the Adi Hindu movement in Uttar Pradesh. This movement had a strong impact on dalits, especially in the years following Ambedkar's conversion to Buddhism. This article examines how Ravidas became the most popular saint among the dalits in Kanpur and how the dalits accepted Buddhism in the 1980s. It also explains the emergence of Navayana Buddhism, which was conceptualised as the total rejection of Hinduism and was institutionalised with a temple and a Buddhist monk, a governing body of lay persons and a canon of public and private rites. - Reproduced.
Keywords: Ambedkar, B.R.; Ravidas; Buddhism